2022
DOI: 10.3390/v14020377
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection of Sertoli Cells Alters Protein Expression Involved in Activated Immune and Antiviral Response Pathways, Carbohydrate Metabolism and Cardiovascular Disease

Abstract: Zika virus (ZIKV), a re-emerging virus, causes congenital brain abnormalities and Guillain–Barré syndrome. It is mainly transmitted by Aedes mosquitoes, but infections are also linked to sexual transmissions. Infectious ZIKV has been isolated, and viral RNA has been detected in semen over a year after the onset of initial symptoms, but the mode of long-term persistence is not yet understood. ZIKV can proliferate in human Sertoli cells (HSerC) for several weeks in vitro, suggesting that it might be a reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Noticeably, Dengue virus (DENV), which is closely related to ZIKV, depends on the glycolysis pathway for its replication ( 45 ), and high glucose levels have been shown to restrict ZIKV infection in human kidney cells ( 46 ). In line with our findings, recent studies in human cells also report dramatic changes in carbohydrate concentrations after ZIKV infection ( 47 ). These alterations target proteins including enzymes, transcription regulators, transporters, and kinases associated with energy generation and immune cell activation.…”
Section: Discussionsupporting
confidence: 93%
“…Noticeably, Dengue virus (DENV), which is closely related to ZIKV, depends on the glycolysis pathway for its replication ( 45 ), and high glucose levels have been shown to restrict ZIKV infection in human kidney cells ( 46 ). In line with our findings, recent studies in human cells also report dramatic changes in carbohydrate concentrations after ZIKV infection ( 47 ). These alterations target proteins including enzymes, transcription regulators, transporters, and kinases associated with energy generation and immune cell activation.…”
Section: Discussionsupporting
confidence: 93%
“…Plant carbohydrate metabolism frequently results in the occurrence of starch lesions or ringspots at the sites of viral infection [ 36 , 37 ]. In humans, carbohydrate metabolism is hijacked by the Zika virus in an effort to usurp the generation of cellular energy [ 38 ]. Fatty acid metabolism contributes to the replication of multiple human viruses, including the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and hepatitis C virus [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of cerebral malaria involves the sequestration of infected erythrocytes in the brain microvasculature and the resulting immune response, leading to endothelial damage, vascular leakage, and hypoxia. These pathological changes can ultimately lead to neurological dysfunction and contribute to the high mortality rate associated with cerebral malaria [ 133 ]. Gene expression profiling studies have identified shared pathways and molecular signatures between cerebral malaria and neurodegenerative diseases, suggesting potential common mechanisms.…”
Section: Immune Evasion In the Vertebrate Hostmentioning
confidence: 99%
“…Brasil et al reported a potential association of ZIKAV infection with congenital heart disorders in infants [ 226 ]. In a recent study, Rashid et al reported that ZIKAV infection of human Sertoli cells significantly altered several proteins involved in cardiac hypertrophy [ 133 ].…”
Section: Immune Evasion In the Vertebrate Hostmentioning
confidence: 99%